IMPAIRMENT OF MALE FERTILITY UNDER THE INFLUENCE OF MUTAGENIC SUBSTANCES CONTAINED IN TOBACCO SMOKE - Abdurakhmanova Dilnoza; Tursunova Irodabonu; Eshmurotov Abdukakhhor; Yusupova Mohira Tolaganovna (Western European Studies, 2025)
Despite the established link between smoking and deterioration of general health, as well as a decrease in male fertility, tobacco continues to be actively consumed throughout the world. The main components of tobacco smoke — nicotine and its metabolite cotinine — are able to penetrate the blood-testis barrier and have a toxic effect on germ cells. There is convincing evidence that smoking reduces sperm concentration and motility, increases the number of cells with pathological morphology, and contributes to genetic and epigenetic disorders. Experimental and clinical studies show DNA fragmentation, genomic instability, mutations and aneuploidies in sperm exposed to tobacco smoke components. The aim of this review is to analyze the mutagenic effect of tobacco components on the male reproductive system, taking into account molecular and epidemiological data.
Keywords: nicotine; sperm; epigenetics